The Shafi'i Madhhab’s Perspective On Maqashid Al-Shari'ah In Relation To Sirri Marriage - Hazarul Aswat; Moh. Fawwaz (CV. Akira Java Bulu, 2025)
Marriage is a sacred bond between a man and a woman who share the same religion, fulfilling the requirements and pillars as prescribed by their respective faiths. This applies equally to Islam, as reinforced by national marriage laws governing such matters. This study examines how unregistered (sirri) marriages are viewed from the perspective of Islamic jurisprudence, specifically through the lens of Maqashid al-Shari’ah within the Shafi'i school of thought (Madhhab of Imam Shafi’i, may Allah have mercy on him). This research uses a qualitative (library research) method by collecting data, identifying key points related to the main issue, interpreting the meaning, and presenting it in a discussion relevant to the core study. The findings show that one of the main objectives of Maqashid al-Shari’ah, namely the protection of lineage (hifz al-nasl), positions marriage as the best means of safeguarding legitimate progeny—as long as the essential requirements and pillars of marriage are fulfilled. This includes sirri marriages, which, though not officially registered with the state and thus lacking legal recognition, may still be religiously valid. Therefore, the Shafi’i school holds that to avoid adultery (zina), a sirri marriage can be considered valid as long as it involves the presence of a guardian (wali) and two witnesses, since both are essential pillars (arkan) of marriage in Islam. This study is both important and distinct because it emphasizes the public good (maslahah) of protecting society from adultery, and it aims to promote a better understanding of this issue among the community